2022
DOI: 10.3390/su14073792
|View full text |Cite
|
Sign up to set email alerts
|

Corporate Social Responsibility Preferences in South Africa

Abstract: What leads firms in South Africa (SA) to prefer specific CSR initiatives over others? The researchers analyzed secondary data from publicly available information of 231 listed firms on the Johannesburg Stock Exchange. To determine national/institutional level preferences, ten CSR activities were identified among all firms and ranked in terms of their mean score of whether each firm participated in an activity or not. To determine industry/stakeholder influence, CSR activities were regressed against the firms’ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 64 publications
0
6
0
1
Order By: Relevance
“…The project has doubled the water supply for the surrounding communities and nearby urban areas [2,103]. The support from various corporations has enabled the Peruvian government to adopt innovative technologies for melting glaciers and cleaning the water to make it safe for both domestic and industrial applications [2,104]. The initiative is designed to increase water supply across the country by more than 20 percent over the next 5 years.…”
Section: Water Stewardshipmentioning
confidence: 99%
See 2 more Smart Citations
“…The project has doubled the water supply for the surrounding communities and nearby urban areas [2,103]. The support from various corporations has enabled the Peruvian government to adopt innovative technologies for melting glaciers and cleaning the water to make it safe for both domestic and industrial applications [2,104]. The initiative is designed to increase water supply across the country by more than 20 percent over the next 5 years.…”
Section: Water Stewardshipmentioning
confidence: 99%
“…In South Africa's Cape Town, water supply to the city's over 4 million residents has become a significant challenge. The city has been grappling with various challenges, including pollution, frequent damage, and climate change [104]. Being a port city, Cape Town should not consider water scarcity as one of its major problems.…”
Section: Water Stewardshipmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, businesses prioritize CSR initiatives that are essential to their closest stakeholders. As a result, companies choose some social and environmental initiatives above others when it comes to CSR [21].…”
Section: Societal Pressures (Ex2)mentioning
confidence: 99%
“…In general, such activities can be seen as a specific field of the corporate social responsibility [46] and they include financing cultural activities, promoting cultural activities in public spaces, creating and maintaining art collections, offering prize awards to outstanding cultural creators or persons and organizations that support the arts and sponsoring the training of young and talented artists. Previous research has found that CSR activities regarding culture are included in the CSR programs of companies-quite often as top priorities [9,[47][48][49][50][51].…”
Section: Sustainability and Csr In The Banking Sectormentioning
confidence: 99%